Assessment of soil vulnerability to erosion in different land surface configurations and management practices under semi-arid monsoon climate - Kumar, G.; Kurothe, R. S.; Viswakarma, A. K.; Mandal, D.; Sena, Dipaka Ranjan; Mandal, U.; Pande, V. C.; Dinesh, D. (Elsevier, 2023)
Soil erosion leads to reduction in land productivity. Concentrated rainfall under monsoon climate increases the erosion vulnerability of poor soils of semiarid regions. Soil vulnerability is the response to impact of slope and land management practices. Assessment of soil vulnerability to soil erosion is crucial for devising an effective soil conservation plan. Therefore, a 7-year long experiment has been initiated for assessing vulnerability to soil erosion for a sandy loam soil using Pearl millet (Pennisetum glaucum) as the test crop in a typical semiarid monsoon climate. In case of runoff, samples were collected and measured every 24 h. These samples were analyzed for sediment, clay, organic carbon (OC), and nitrogen content. A positive linear relation between rainfall and runoff at 2% slope (R2 : 0.58–0.72), curvilinear relation at higher slope (R2 : 0.81–0.86), and positive linear relationship between runoff and soil loss (R2 : 0.47–0.64) were observed. An increase in slope length from 11 to 66 m increased runoff and soil loss by 1.62 times and 1.72 times, respectively. Similarly, an increase in slope steepness from 2% to 9% increased runoff and soil loss by 1.84 times and 3.84 times, respectively. In response to the 56.4% of the total rainfall received, the contribution of runoff and soil loss during the initial 30 days of the crop growing period to the total runoff and soil loss was 68–74% and 80–90% respectively. Sediments were enriched with organic carbon (1.62–3.12) and clay content (1.14–1.55), however, enrichment ratios reduced with the increase in slope. The total loss of nitrogen through erosion had a positive correlation with the sediment loss. Manure and mineral fertilizer application in pearl millet reduced the mean seasonal runoff by 14.4–24.8% and soil loss by 22.7–32.6%. Under bare soil conditions, application of manure and fertilizers reduced runoff by 6.4–8.7% and soil loss by 6.5–7.8%. The knowledge derived from this study can thus improve our understanding of hydrological responses and erosion process of both land configuration and land management practices. The data generated in the study is an important starting point to develop concepts for better management and effective mitigation of land degradation. The findings also suggest the need of initial soil cover, minimum soil disturbance at steeper slope (>3%) and need of conservation measures even on the milder slope (= 3%).